2017
DOI: 10.3390/foods6080061
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Fat Quality and Conjugated Linoleic Acid Content of Dairy Products from the Tropics: Evidence of Potential Impact on Human Health

Abstract: Seasonal variation in conjugated linoleic acid (CLA) content and atherogenicity index (AI) of retail dairy products (whole milk, butter, and prato, a soft yellow cheese) from Brazil was investigated. CLA content of dairy products ranged from 0.55 to 1.53 g CLA/100 g fatty acids and was on average 25% higher during the rainy season compared to the dry season. Dairy products from the rainy season also had lower AI levels, indicating a lower risk of causing cardiovascular disease in consumers. This seasonality le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
(61 reference statements)
2
1
0
2
Order By: Relevance
“…The total polyunsaturated fatty acids (PUFA), linoleic (C18:2), linolenic acid (C18:3) acid and conjugated linoleic acid ratio of the samples was found between 3.86-3.89 %, 1.89-2.29 %, 0.95-0.97 % and 0.84-0.85 %, respectively. Similar to the results obtained in this study, the total PUFA, linoleic and linolenic acid ratios of butter were reported as 2.07 %, 0.46 % and 2.63 %, respectively (Nunes et al, 2017).…”
Section: The Fatty Acid Composition Of Sanliurfa Butterfatsupporting
confidence: 89%
See 1 more Smart Citation
“…The total polyunsaturated fatty acids (PUFA), linoleic (C18:2), linolenic acid (C18:3) acid and conjugated linoleic acid ratio of the samples was found between 3.86-3.89 %, 1.89-2.29 %, 0.95-0.97 % and 0.84-0.85 %, respectively. Similar to the results obtained in this study, the total PUFA, linoleic and linolenic acid ratios of butter were reported as 2.07 %, 0.46 % and 2.63 %, respectively (Nunes et al, 2017).…”
Section: The Fatty Acid Composition Of Sanliurfa Butterfatsupporting
confidence: 89%
“…The ratios of palmitic, stearic and myristic acids of Samn were reported as 35.13 %, 15.51 % and 13.24 %, respectively (Mariod et al, 2010). Similar to the results obtained in this study, the ratios of SFA, palmitic, stearic and myristic acid of butter sold in markets of Rio de Janeiro/Brazil were reported as 63.2 %, 31.4 %, 11.7 % and 11.5 %, respectively (Nunes et al, 2017). Compared to the results obtained in this study, the total SFA, myristic and palmitic acid of traditional Tibetan ghee was reported as 40.99 g/100 g, 3.92-9.85 g/100 g and 22.19-28.04 g/100 g, respectively (Jing et al, 2019).…”
Section: The Fatty Acid Composition Of Sanliurfa Butterfatsupporting
confidence: 87%
“…В зависимости от соотношения жирных кислот меняется содержание твердых жиров в масле [9], что, в свою очередь, оказывает влияние на температуру плавления масла и такой немаловажный показатель, как термоустойчивость, который характеризует степень изменения площади поверхности масла при выдерживании при температуре 30 °C [2].…”
Section: материалы и методы исследованияunclassified
“…Химический состав жира зависит от породы коров, состава кормовой базы, сезона сбора молока, а также от технологии изготовления сливочного масла. Так, например, кормовая база и сезон сбора молока влияют на профиль жирных кислот: чем больше в рационе скота травы, тем больше ненасыщенных жирных кислот в составе триглицеридов молочного жира [2]. Следовательно, содержание твердых фракций жира будет меньше, что отразится на термоустойчивости сливочного масла [3].…”
Section: Introductionunclassified
“…Those vitamins and minerals pose anticarcinogenic properties via inducing cell cycle arrest, apoptosis and differentiation while suppressing angiogenesis, invasion and metastasis (21)(22)(23)(24) . Further, dairy products include large amounts of lactic acid bacteria and conjugated linoleic acids (25)(26)(27) . Lactic acid bacteria help in enhancing the host's immune response, inducing antioxidative and antiproliferative functions and detoxifying toxicants formed during food processing, characteristics that have been proven to prevent cancer (28)(29)(30) .…”
mentioning
confidence: 99%